Marketing and finance : working the interface - Walters, David. (Allen and Unwin, 1997)
This book is divided into three parts: Marketing and finance interface issues for Marketing Strategy, Analysis and Decisions; Cost Implications and Cost Characteristics affecting marketing strategy decisions; a,d Financial Structure and Performance characteristics.